Pengaruh Parenting Orangtua Terhadap Perilaku Penyimpangan Seksual Pada Anak - Yemima Grace Sianipar; Sri Marlinda; Berlianta Br Surbakti; Nur Amanda Pratiwi; Utami Nurhafsari Putri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Sexual deviation among children has become an increasingly concerning issue, particularly in the era of rapid technological advancement and unrestricted access to information. One of the most influential factors contributing to this problem is parenting style. This study aims to analyze the influence of parenting on sexual through a qualitative literature review. Data were obtained from scientific journals published within the last five years discussing parenting patterns, sexual education, parental supervision, and emotional involvement in shaping children’s sexual behavior. The findings reveal that inconsistent parenting, poor communication, inadequate supervision, and the lack of sexual education significantly increase children’s vulnerability to deviant sexual behavior. Conversely, democratic parenting characterized by warmth, proportional supervision, and appropriate sexual education effectively reduces the risk of deviant behavior and enhances children’s ability to recognize and avoid unsafe situations. Therefore, it can be concluded that proper parenting serves as a fundamental component in fostering healthy sexual understanding and in preventing sexual deviance among children.